Notes on a scandal [videorecording (DVD)] - Eyre, Richard, 1943-; Dench, Judi, 1934-; Blanchett, Cate, 1969-; Georgeson, Tom (20th Century Fox Home Entertainment, 2007)
Barbara is a cynical schoolteacher who is close to retirement. Her only means of taking the edge off her desperate loneliness is writing in her journal. Sheba is a younger, attractive woman, who joins the faculty as an art teacher. Barbara watches her from afar and has nothing but caustic things to say in her diary. Barbara finds herself reaching out to Sheba. Sheba responds by inviting her to dinner at her house to meet Sheba's lecturer husband and their two children. Later, when Barbara discovers that Sheba is having a sexual relationship with a 15-year old student, Barbara realizes that knowledge of this secret gives her power over Sheba which she can use for her own purposes. Sheba becomes uneasy with Barbara's friendship. The tenuous relationship between the two women reaches a crisis point when Barbara's cat is dying and she asks Sheba to go with her to the vet. Sheba chooses to go with her family to see their son in a play instead. In revenge, Barbara sets in motion the scandal that will rock both their lives in ways they never imagined.